Multi-structural evolution of conductive reactive powder concrete manufactured by enhanced ohmic heating curing. (October 2021) - Tian, Weichen; Liu, Yushi; Wang, Wei
Abstract: This work presented an enhanced ohmic heating (OH) curing method to promote the ultra-high strength of conductive hybrid carbon fibers reinforced RPC (HCF-RPC). This novel curing method was conducted at normal pressure and temperature, but its curing performance was comparable to the autoclave (AC) curing that required strict equipment to provide high pressure and temperature. Hybrid carbon fibers (CFs) and carbon nanofibers (CNFs) were synergistically applied to enhance electric conductivity and heating efficiency of HCF-RPC. Effects of enhanced OH curing on the multi-structural evolution of RPC were clarified and further compared with AC and high temperature stream (HTS) curing. The results showed that enhanced OH curing endowed the curing temperature of 180 °C to stimulate the compressive strength of HCF-RPC to 104.5 MPa with ultrashort curing duration of 3 h. XRD and TG analyses demonstrated the promoted hydration effect of enhanced OH curing, additional hydration products (tobermorite and xonotlite) were only detected in the enhanced OH and AC cured samples. Furthermore, 29 Si NMR data revealed longer average chain length in the enhanced OH cured sample than that of the AC cured sample. Additionally, a refined micro- and meso-scale pore structure was observed in the enhanced OH cured samples from MIP and BET analyses. This work presents enhanced OH curing as an effective method to replace traditional heat treatment methods to rapidly prepare RPC structure.